Genome-Wide Association Study Meta-Analysis for Parkinson Disease Motor Subtypes. (April 2021) - Alfradique-Dunham, Isabel; Al-Ouran, Rami; von Coelln, Rainer; Blauwendraat, Cornelis; Hill, Emily; Luo, Lan; Stillwell, Amanda; Young, Emily; Kaw, Anita; Tan, Manuela; Liao, Calwing; Hernandez, Dena; et al.
Abstract : Objective: To discover genetic determinants of Parkinson disease (PD) motor subtypes, including tremor dominant (TD) and postural instability/gait difficulty (PIGD) forms. Methods: In 3, 212 PD cases of European ancestry, we performed a genome-wide association study (GWAS) examining 2 complementary outcome traits derived from the Unified Parkinson's Disease Rating Scale, including dichotomous motor subtype (TD vs PIGD) or a continuous tremor/PIGD score ratio. Logistic or linear regression models were adjusted for sex, age at onset, disease duration, and 5 ancestry principal components, followed by meta-analysis. Results: Among 71 established PD risk variants, we detected multiple suggestive associations with PD motor subtype, including GPNMB ( rs199351, p subtype = 0.01, p ratio = 0.03), SH3GL2 ( rs10756907, p subtype = 0.02, p ratio = 0.01), HIP1R ( rs10847864, p subtype = 0.02), RIT2 ( rs12456492, p subtype = 0.02), and FBRSL1 ( rs11610045, p subtype = 0.02). A PD genetic risk score integrating all 71 PD risk variants was also associated with subtype ratio ( p = 0.026, ß = −0.04, 95% confidence interval = −0.07–0). Based on top results of our GWAS, we identify a novel suggestive association at the STK32B locus (rs2301857, p ratio = 6.6 × 10 −7 ), which harbors an independent risk allele for essential tremor. Conclusions: Multiple PD risk alleles may also modify clinical manifestations to influence PD motor subtype. The discovery of a novel variant at STK32B suggests a possible overlap between genetic risk for essential tremor and tremor-dominant PD.